Gambaran Status Gizi Penderita Tumor Otak Primer dan Metastasis serta Faktor-faktor yang Memengaruhinya - Aninditha, Tiara; Tanjung, Gloria; Andayani, Diyah Eka; Aman, Renindra Ananda; Estiasari, Riwanti; Yanuar, Ahmad; Sofyan, Henry Riyanto (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2022)
Introduction: According to the pathophysiology, weight loss is a specific marker for suspected malignancy. However, this is rarely found in cases of brain tumors. The presence of the blood brain barrier is thought to play a role in differentiating nutritional status in primary and metastatic brain tumors. Therefore, it is necessary to do this research. Aim: Knowing the description, prevalence, differences in nutritional status of patients with primary and secondary brain tumors, and the affecting factors. Methods: Cross-sectional study in patients with primary and secondary brain tumors at Cipto Mangunkusumo General Hospital in 2017-2019. Malnutrition was diagnosed using the GLIM (Global Leadership Initiative on Malnutrition) criteria. Data analysis used Chi-Square/Fisher and multivariate logistic regression. There were 333 subjects: 246 primary and 87 secondary brain tumors. Description of nutritional status of patients with primary brain tumors: 47.6% obese; 6.1% malnutrition; the rest were normal, while in secondary brain tumors: 25.3% were malnourished; 24.1% obese; the rest is normal. Secondary brain tumor at risk of malnutrition with RR 1.257 (95% KI 1.108-1.426), p<0.001. Factors influencing malnutrition were the type of primary/secondary brain tumor, gender, age, decreased consciousness, anorexia, gastrointestinal complaints, intraaxial lesions, multiple lesions, and the location of the lesions involving the frontal lobes. The independently related factor was multiple lesions with an aOR of 3,423 (95% KI 1.124-10.426), p 0.03. Conclusion: The nutritional status of patients with primary and secondary brain tumors was different, with higher levels of malnutrition in secondary brain tumors and higher obesity in primary brain tumors. The number of multiple lesions in the brain affects the occurrence of malnutrition.